2014
DOI: 10.1007/s10096-014-2247-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in previously healthy children in Emergency Departments: clinical and microbiological characteristics and outcome

Abstract: A blood culture (BC) is frequently requested in both patients with a suspected occult bacteremia/invasive infection as well as those with certain focal infections. Few data are available on the characteristics of patients in whom a bacteremia is identified in the Pediatric Emergency Department (PED). A prospective multicenter registry was established by the Spanish Pediatric Emergency Society. Epidemiological data, complementary test results, clinical management, and final outcome were recorded. Data from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
6
29
0
5
Order By: Relevance
“…17 Indeed 1 of the most frequent IBI in young febrile infants is UTI with associated bacteremia. 23,24 In our study, general appearance, age, and urine dipstick identified almost 80% of the IBI patients and, more interestingly, 85% of the sepsis and 90% of the bacterial meningitis. young febrile infants.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…17 Indeed 1 of the most frequent IBI in young febrile infants is UTI with associated bacteremia. 23,24 In our study, general appearance, age, and urine dipstick identified almost 80% of the IBI patients and, more interestingly, 85% of the sepsis and 90% of the bacterial meningitis. young febrile infants.…”
Section: Discussionsupporting
confidence: 54%
“…Improvement in the perinatal antibiotic prophylaxis has reduced the incidence of S. agalactiae early-onset sepsis, 35 -37 E coli is nowadays the leading cause of bacteremia in this population, 6,7,17,24 and Listeria is rarely involved. 6,7,17,24 On the other hand, new biomarkers that have been shown to be better predictors of IBI have been included in many management protocols. Curiously, the Lab-score, developed less than 10 years ago, revealed a lower performance compared with previously published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with occult bacteremia had higher mean temperature (40.2 C ± 0.5 C) when compared with patients with negative or contaminated cultures (p value < 0.001) [31]. The introduction of the heptavalent pneumococcal conjugate vaccine (PCV7) led to further declines in the overall rates of occult bacteremia to <0.5-1% [83,84].…”
Section: Occult Bacteremiamentioning
confidence: 99%
“…Occult bacteremia may represent a lag in the clinical manifestation of the disease, and this has been documented in various studies [83][84][85][86]. It is difficult to ascertain the seriousness of occult bacteremia, but biomarkers such as neutrophil count, CRP and PCT are useful analytical parameters [84,85].…”
Section: Occult Bacteremiamentioning
confidence: 99%
See 1 more Smart Citation